colorimetric photoelastic analysis of tension distribution around dental implants - João César Zielak; Marcelo Filietaz; Felipe Belmonte Archetti; Paulo Roberto Camati; Thalyta Verbicaro; Ricardo Scotton; Adilson Yoshio Furuse; Carla Castiglia Gonzaga (Revista Sul-Brasileira de Odontologia, 2014)
To demonstrate a colorimetric photoelastic analysis of tension distribution around dental implants under axial loads. Material and methods: Eight different designs of implant from two manufacturers were connected to their abutments, placed into epoxy resin blocks and observed under a polariscope coupled to a universal testing machine while subjected to axial loads of 5 N. The obtained images were quantitatively analyzed by image analysis software. Results: A strong correlation was found between the surface area and the implant fringe transition area (magenta color) of most samples (r = 0.908), and a moderate correlation was found between the fringe transition area and the mean thread height of the implants (r = 0.706, or r = 0.768 using a quadratic function). Conclusion: By this biomechanical study, it was possible to demonstrate a correlation of some implant characteristics to the colored fringe areas of tension distribution, a colorimetric method that can be used in comparative studies of photoelastic analysis. Clinical significance: An accurate planning and knowledge of oral implant biomechanics is important so that a safe and long-lasting